Efficacy of a 2-Month Very Low-Calorie Ketogenic Diet (VLCKD) Compared to a Standard Low-Calorie Diet in Reducing Visceral and Liver Fat Accumulation in Patients With Obesity - Cunha, Guilherme Moura; Guzman, German; Correa De Mello, Livia Lugarinho; Trein, Barbara; Spina, Luciana; Bussade, Isabela; Marques Prata, Juliana; Sajoux, Ignacio; Countinho, Walmir (Frontiers in Endocrinology, 2020)
BBackground: Currently the treatment of nonalcoholic fatty liver disease (NAFLD) is based on weight loss through lifestyle changes, such as exercise combined with calorie-restricted dieting. Objectives: To assess the effects of a commercially available weight loss program based on a Very Low-Calorie Ketogenic Diet (VLCKD) on Visceral Adipose Tissue (VAT) and liver fat content compared to a standard Low-Calorie diet (LC). As a secondary aim we evaluated the effect on liver stiffness measurements. Methods: Open, randomized, controlled, prospective pilot study. Patients were randomized and treated either with a LC or a VLCKD and received orientation and encouragement to physical activity equally for both groups. VAT, liver fat fraction and liver stiffness were measured at baseline and after 2 months of treatment using Magnetic Resonance Imaging (MRI). Paired t-tests were used for comparison of continuous variables between visits and unpaired test between groups. Categorical variables were compared using the Chi-squared test. Pearson’s correlation was used to assess the association between VAT, anthropometric measures and hepatic fat fraction. A significance level of the results was established at p<0.05. Results: 39 patients (20 with VLCKD and 19 with LC) were evaluated at baseline and 2 months of intervention. Relative weight loss at 2 months was -9.59 ± 2.87 % in the VLCKD group and -1.87 ± 2.4 % in the LC group (p<0.001). Mean reductions in VAT were -32.0 cm2 for VLCKD group and -12.58 cm2 for LC group (p<0.05). Reductions in liver fat fraction were significantly more pronounced in the VLCKD group than in LC group (4.77% vs 0.79%; p<0.005). Conclusion: Patients undergoing a VLCKD achieved superior weight loss, with significant VAT and liver fat fraction reductions when compared to standard the low-calorie diet. The weight loss and rapid mobilization of liver fat demonstrated with VLCKD, could serve as an effective alternative for the treatment of NAFLD.